THE EFFECT OF APPRECIATION, COMPETENCE, PROFESSIONALISM AND LEADERSHIP QUALITY ON THE PERFORMANCE OF EMPLOYEES OF PT. TIGA SERANGKAI SURAKARTA - Syahdan AN; Istiatin Istiatin; Sudarwati Sudarwati (JEMMA (Journal of Economic, Management and Accounting), 2023)
Professionalism, and Leadership Quality on Employee Performance at PT Tiga Serangkai Surakarta. This research makes use of three different types of independent variables, namely Awards, Competence, Professionalism, and Leadership Quality with one variable dependent, namely Employee Performance. Participants in this study's population were all employees of PT. Tiga Serangkai Surakarta and the sample used in this study was 91 employees. The questionnaires were distributed among 91 employees of PT. Tiga Serangkai Surakarta. Data were processed using SPSS. The approach to data analysis that was taken for this investigation uses multiple regression analysis.Â These are the findings of the investigation indicate thatÂ : Awards has a positive effect on employee performance, Competence has a positive effect on employee performance, Professionalism has a positive effect on employee performance, and Leadership quality has a positive effect on employee performance